Kaposi Sarcoma-Associated Herpesvirus Infection and Endemic Burkitt Lymphoma. (19th February 2020) - Oluoch, Peter O; Oduor, Cliff I; Forconi, Catherine S; Ong'echa, John M; Münz, Christian; Dittmer, Dirk P; Bailey, Jeffrey A; Moormann, Ann M
Abstract: Background: Endemic Burkitt lymphoma (eBL) is associated with Epstein-Barr virus (EBV) and Plasmodium falciparum malaria coinfections. However, the role of Kaposi sarcoma-associated herpesvirus (KSHV), also endemic in Africa, has not been evaluated as a cofactor in eBL pathogenesis. Methods: Multiplexed seroprofiles for EBV, malaria, and KSHV were generated for 266 eBL patients, 78 non-eBL cancers, and 202 healthy children. KSHV and EBV loads were quantified by PCR. Results: KSHV seroprevalence did not differ by study group but was associated with age. Seropositivity, defined by K8.1/LANA or in combination with 5 other KSHV antigens (ORF59, ORF65, ORF61, ORF38, and K5) was associated with antimalarial antibody levels to AMA1 (odds ratio [OR], 2.41, P < .001; OR, 2.07, P < .001) and MSP1 (OR, 2.41, P = .0006; OR, 5.78, P < .001), respectively. KSHV loads did not correlate with antibody levels nor differ across groups but were significantly lower in children with detectable EBV viremia ( P = .014). Conclusions: Although KSHV-EBV dual infection does not increase eBL risk, EBV appears to suppress reactivation of KSHV while malaria exposure is associated with KSHV infection and/or reactivation. Both EBV and malaria should, therefore, be considered as potential effect modifiers for KSHV-associated cancers in sub-Saharan Africa. Abstract : Kaposi sarcoma-associated herpesvirus (KSHV) and Epstein-Barr virus (EBV) dual infections in African children do not increase the risk of endemic Burkitt lymphoma. However, KSHV reactivation is positively associated with Plasmodium falciparum infections and inversely associated with EBV load.